2022
DOI: 10.1161/strokeaha.121.037061
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Intravenous Alteplase, Early Reperfusion, and Clinical Outcome in Patients With Large Vessel Occlusion Stroke: Post Hoc Analysis of the Randomized DIRECT-MT Trial

Abstract: Background: The added value of intravenous alteplase in reperfusing ischemic brain tissue in patients undergoing endovascular treatment and directly presented to an endovascular treatment-capable hospital is uncertain. We conducted this post hoc analysis of a randomized trial (DIRECT-MT [Direct Intraarterial Thrombectomy in Order to Revascularize Acute Ischemic Stroke Patients With Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals: A Multicenter Randomized Clinical Trial]) to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 24 publications
3
27
2
Order By: Relevance
“…No interaction could be detected with the secondary safety outcomes, and pharmacological and technical efficacy. However, a sub-analysis of the DEVT trial recently reported an association of bridging IVT with increased early reperfusion when MT was delayed more than approximately half an hour 20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No interaction could be detected with the secondary safety outcomes, and pharmacological and technical efficacy. However, a sub-analysis of the DEVT trial recently reported an association of bridging IVT with increased early reperfusion when MT was delayed more than approximately half an hour 20…”
Section: Discussionmentioning
confidence: 99%
“…However, a sub-analysis of the DEVT trial recently reported an association of bridging IVT with increased early reperfusion when MT was delayed more than approximately half an hour. 20 Analysis of in-hospital delays revealed a potential heterogeneity of treatment effect of IVT regarding mortality and mRS shift analysis, with a larger proportional benefit seen when DTN was shorter. However, the credibility of those subgroup effects is unclear because of multiple testing and hence, this finding might be due to chance.…”
Section: Ischemic Strokementioning
confidence: 99%
“…The area surrounding the core infarct, which is vulnerable to blood flow and metabolic changes, is called the "ischemic penumbra" region (16,33). Salvaging the ischemic penumbra by IVT or EVT seems to lead to better clinical outcomes (8,9,34). PET studies have found that most patients have ischemic penumbra lasting up to 18 h, which provides a theoretical window for the effective treatment of AIS (33).…”
Section: Exploration Of Hyperbaric Oxygen Therapy In Animal Modelsmentioning
confidence: 99%
“…11 A recent subanalysis of this trial showed that pre-interventional reperfusion occurred more often in patients randomized to the IVT+MT arm, especially when the interval between IVT administration and groin puncture was more than half an hour. 17 To elucidate the association between IVT, pre-interventional reperfusion, and clinical outcomes, we have performed a post-hoc analysis of the Solitaire With the Intention For Thrombectomy Plus Intravenous t-PA versus DIRECT Solitaire Stentretriever Thrombectomy in Acute Anterior Circulation Stroke (SWIFT DIRECT) trial. 10…”
Section: Ischemic Strokementioning
confidence: 99%